2005
DOI: 10.1074/jbc.m508007200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclin-dependent Kinase 1 Induces Cytokinesis without Chromosome Segregation in an ECT2 and MgcRacGAP-dependent Manner

Abstract: Cleavage furrow formation marks the onset of cell division during early anaphase. The small GTPase RhoA and its regulators ECT2 and MgcRacGAP have been implicated in furrow ingression in mammalian cells, but the signaling upstream of these molecules remains unclear. We now show that the inhibition of cyclin-dependent kinase (Cdk)1 is sufficient to initiate cytokinesis. When mitotically synchronized cells were treated with the Cdk-specific inhibitor BMI-1026, the initiation of cytokinesis was induced precocious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 34 publications
(45 reference statements)
8
75
0
Order By: Relevance
“…However, DNA, even if it begins to segregate between these daughter cells, seems to be trapped in the midzone. This phenomenon is readily comparable to the phenotype described after CDK1 chemical inhibition by BMI-1026 or RO-3306 (Seong et al, 2003;Niiya et al, 2005;Vassilev et al, 2006). However, in our case, the chromosomes eventually collapse, giving rise to a single tetraploid nucleus.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, DNA, even if it begins to segregate between these daughter cells, seems to be trapped in the midzone. This phenomenon is readily comparable to the phenotype described after CDK1 chemical inhibition by BMI-1026 or RO-3306 (Seong et al, 2003;Niiya et al, 2005;Vassilev et al, 2006). However, in our case, the chromosomes eventually collapse, giving rise to a single tetraploid nucleus.…”
Section: Resultssupporting
confidence: 91%
“…Under nocodazole treatment, BMI-1026 leads to mitosis exit and cell spreading without division. Depending on the nocodazole concentration, cells can show membrane blebbing, which is assumed to represent a cortical activity of actomyosin contraction subsequent to formation of ectopic cleavage furrows (Seong et al, 2003;Niiya et al, 2005). Our observation of precocious mitosis exit and abnormal cytokinesis in proliferating cells downregulated for cyclins B1 and B2 fully reproduces these phenotypes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Control cells entered anaphase 1-3 h after nocodazole release, and 88% (n ϭ 65) of the cells completed normal mitosis and cytokinesis within 4 h (Figure 10, C and D, a; and Movie S7). Like other Cdk1 inhibitors (Niiya et al, 2005), roscovitine promoted premature exit from mitosis (Movie S8). The cells formed ectopic furrows ( Figure 10C, b, arrows) and exhibited cortical contraction (81%; n ϭ 115).…”
Section: Bundled Microtubules Direct the Furrowing Site Via Rhomediatmentioning
confidence: 99%
“…Inactivation of Cdk1/cyclin B regulates the timing of mitotic exit and cytokinesis as well as the mitotic spindle array (Wheatley et al, 1997;Echard and O'Farrell, 2003;Mishima et al, 2004). Recently, it has been reported that the Cdk1 inhibitors BM-1026 and purvanalol A promote premature mitotic exit and furrow ingression (Niiya et al, 2005). To test whether the Cdk1 inhibitor roscovitine affects initiation of cytokinesis, we treated synchronized prometaphase cells with DMSO (control) or roscovitine (Figure 10A, a and b).…”
Section: Bundled Microtubules Direct the Furrowing Site Via Rhomediatmentioning
confidence: 99%